RETRACTED: LncRNA SNHG19 Promotes the Development of Non-Small Cell Lung Cancer via Mediating miR-137/E2F7 Axis - Zhao, Guang-Yin; Ning, Zhao-Feng; Wang, Rui (Frontiers in Oncology, 2021)
OBJECTIVE: Non-small cell lung cancer (NSCLC) is a common malignant tumor, which has high incidence and low the 5-year survival rate. Long noncoding RNAs (lncRNAs) play critical roles in carcinoma occurrence and metastasis. Herein, our aim was to investigate the effects of lncRNA SNHG19 in NSCLC progression. MATERIALS AND METHODS: Long non-coding RNA Small Nucleolar RNA Host Gene 19 (lncRNA SNHG19) expression level was measured by bioinformatics and qRT-PCR. Edu, Transwell, and scratch assay were perfomed to explore the role of si-SNHG19 or SNHG19 on NSCLC progression. Luciferase assay was used to verify the relationship between SNHG19/E2F7 with miR-137. The experiment of Xenograft used for exploring the function of SNHG19 in vivo. RESULTS: SNHG19 was upregulated in cancer tissues, patients plasma and cell lines of NSCLC. Knockdown of SNHG19 inhibited cell proliferation, migration and invasion. Luciferase assay performed that SNHG19 regulated E2F7 expression via interacting with miR-137. Overexpression of SNHG19 accelerated NSCLC tumor progression via miR-137/E2F7 axis both in vitro and in vivo. CONCLUSIONS: Our results clarified the SNHG19 function for the first time, and SNHG19 promoted the progression of NSCLC, which was mediated by miR-137/E2F7 axis. This study might provide new understanding and targets for NSCLC diagnosis and treatment.